Hedging by the Gaya Confederacy of Korea: Historical Lessons for Contemporary East Asia? - Brendan M HOWE (East Asian Policy)
Hedging is an essentially contested concept. Originally borrowed from the discipline of economics, it has become prevalent in the discourse on policy prescription in the Asia-Pacific. It is most often referenced with regard to geopolitical challenges of great power contestation faced by secondary powers in Northeast and Southeast Asia. Hedging is often regarded as a strategy to maintain relevance and autonomy in the face of competition between the United States and China. This article investigates the prevalence of hedging in the East Asian region, followed by a case analysis of Gaya. The author offers policy recommendations based on insights gained from ancient Gaya. He argues that, like the polities of the Gaya confederacy, contemporary second-tier states in the Asia-Pacific should cooperate closely, with the common objective of navigating the US–China rivalry. By ensuring their survival and prosperity, they can also contribute to the development of a geopolitical environment characterised by “co-existence”.